The d-t relationship over a century of swimming olympic performances. A limit of the critical velocity concept. - Dekerle, J.; Carter, H. (First international symposium sciences and practices in swimming, 2006)
This study aims to analyse the evolution of the slope (CV, Critical Velocity) and the y-intercept (ADC, Anaerobic Distance Capacity) of the linear d-t relationship over a Century of Olympic swimming performances. The d-t relationship at each Olympic Games (1904-2004) was plotted using the performances of the 100-, 400-, and 1500-m swims. CV and ADC values were determined by linear modelling. Performances always improved between two successive Olympic Games. The systematic increase of CV every 4 years (the 1904 values equal to 51.1% the 2004 values) is in accordance with the literature (Peronnet and Thibaut, 1989) and suggests that 'human aerobic endurance' has improved within the Century. ADC tends to decrease from 1904 to 1976 (-70%) to then increase to 2004 (+33%). The decrease of ADC in the first three quarters of the Century appears difficult to explain and could demonstrate a limit in the use of a mathematical model to fit physiological data.